Influence of products and principles of sharia bank on customer decision with perception as intervening variable in Bank Jambi Syariah - Dahmiri Dahmiri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
This study aims to analyze the influence of sharia bank products and the principles of sharia banks on customer decisions with perception as an intervening variable in Bank Jambi Syariah. Questionnaires were distributed to 301 customers. Analytical tool used is Structural Equation Modeling (SEM) analysis. The results indicate that sharia bank products, principles of sharia banks, and customer perceptions significantly influence both partially and simultaneously on the decision of Bank Jambi Syariah customers. Indirectly, products and principles of sharia bank significantly influence Bank Jambi Syariah customer decisions through customer perception. The dominant variable influencing customer decision is the principles of sharia bank. The originality of the model is reflected on the addition of an intervening variable, showing that there is a greater impact on the customer decision by including perception compared to the impact without including customer perception